2011
DOI: 10.4103/0970-4388.90749
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and neglect

Abstract: Child abuse and neglect are important public health problems and recent estimates of their prevalence suggest that they are considerably more common than had hitherto been realized. Intervening to change parenting practices may, however, be important in their treatment. Despite their frequent occurrence among dental patients, neglect is the least known and identified type of abuse. The present case reports a 3-year-old girl suffering from abuse and neglect. The girl had dental neglect and also performed poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Child neglect is a significant issue in respect to prevalence, incidence, and consequences ( 1 , 8 ). It is a serious problem related to children as the most vulnerable population ( 9 ). The consequences may be real or potential in nature ( 10 ).…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Child neglect is a significant issue in respect to prevalence, incidence, and consequences ( 1 , 8 ). It is a serious problem related to children as the most vulnerable population ( 9 ). The consequences may be real or potential in nature ( 10 ).…”
Section: Contextmentioning
confidence: 99%
“…The consequences may be real or potential in nature ( 10 ). It may originate from ethnic, race, socioeconomic, cultural, religious and educational backgrounds ( 9 , 11 - 13 ). In spite of its high prevalence, it is the least diagnosed ( 9 , 14 , 15 ).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, craniofacial, head, face, and neck injuries occur in 50-75% of all cases of physical child abuse, which may be associated with other injuries elsewhere on the child’s body ( 23 ); however, Jenny et al ( 24 ) revealed that 31% of infants and young children with abusive craniofacial trauma were initially misdiagnosed. Therefore, a careful and thorough intraoral and perioral assessment is always required in all cases of suspected abuse ( 25 - 27 ). Accidental injuries to the oral cavity, face, and head must be distinguished from those caused by abuse, by establishing whether the history, timing, and mechanism of the injury is consistent with the injury type and child’s developmental capabilities ( 26 , 28 ).…”
Section: Introductionmentioning
confidence: 99%